ANALISIS VOLATILITAS IMBAL HASIL REKSADANA SAHAM (STUDI KASUS PADA REKSADANA SCHRODER DANA PRESTASI PLUS) - Ari Yulianto; Heri Ispriyahadi (STIE Muhammadiyah Jakarta, 2020)
This research aims to analyze the empirical evidence of the volatility of stock mutual fund returns. The data used is the daily yield data of Schroder Dana Prestasi Plus mutual funds. The analytical methods used in this study are GARCH (Generalized Auto Regression Heteroscedasticity) and EGARCH (Exponential Generalized Auto Regitional Heteroscedasticity). The results showed that the yield of Schroder Dana Prestasi Plus stock mutual funds proved significantly that there was a time varying volatility phenomenon. Then the volatility in the yield of Schroder Dana Prestasi Plus stock mutual funds was proven to be significantly unaffected by the asymmetric behavior therein. And the level of persistence in the volatility is quite low.